A study on the impact of life meaning on occupational identity of nursing students in China:a cross-sectional study - Lingjing Qiu; Qunfang Miao; Yueyan Zhao; Li Zhu; Yanling Wang (BMC, 2023)
Abstract Background With the alterations of the Chinese epidemic prevention policy, China experienced a nationwide wave of the Coronavirus disease 2019 (COVID-19) pandemic from December 2022 to January 2023.The impact of the COVID-19 pandemic extends beyond individual perceptions of the meaning of life and attitudes toward life and death; it also affects the professional identity of nursing students.This study explored nursing students' professional identity and life meaning of affected by the pandemic. Methods An online survey was conducted using the Chinese version of the Nursing Student Career Identity Scale and the Chinese version of the Meaning in Life Questionnaire to assess the current status of nursing students' professional identity and sense of life meaning. Data were also collected on participant gender, education, clinical practice experience, and COVID-19 infection. Results The scores for nursing students' sense of professional identity (61.58 ± 16.16) and sense of life meaning (45.29 ± 12.65) were both at an intermediate level. Compared to the scores before the COVID-19 pandemic, Chinese nursing students' professional identity scores increased, while their sense of life meaning scores decreased. Moreover, we found a positive correlation between professional identity and sense of life meaning (p < 0.001); nursing students exhibited a stronger professional identity when they had a relatively higher sense of life meaning than those with a relatively lower sense of life meaning. Conclusion Enhancing nursing students' sense of meaning in life is crucial for maintaining their professional identity. Attention should be given to life education for nursing students and the development of relevant educational curricula.